Numerical study on flow and heat transfer characteristics of R1233zd(E) cooled in horizontal circular tubes under supercritical pressure. (5th January 2023) - Jia, Cheng-Qi; Hu, Peng; Zhou, Min-Shan; Jiang, Yi-Ran; Zhao, Pan-Pan; Jia, Lei
Highlights: The flow and heat transfer of supercritical R1233zd(E) in tubes are studied. The effects of ρ and cp on the heat transfer performance of fluid are discussed. The tube wall has a continuous response to the change of internal fluid. The effect of buoyancy is explored and the thresholds of criteria are obtained. A new heat transfer correlation for supercritical R1233zd(E) is developed. Abstract: Supercritical organic refrigerants have been widely used in energy conversion and waste heat recovery systems due to their excellent heat transfer characteristics. R1233zd(E), as a fourth-generation environmentally friendly alternative refrigerant, has extensive application prospects. However, there is a lack of research on the heat transfer of supercritical R1233zd(E). In this work, the flow and heat transfer characteristics of supercritical R1233zd(E) in horizontal cooling tubes, including a mini tube and three ordinary tubes, are numerically simulated. In the simulation, not only the wall thickness but also the temperature-dependent thermophysical properties of the tube wall material are considered. The simulated results indicate that the specific heat capacity distributions determine that the peak of the overall heat transfer coefficients appears at a temperature higher than the pseudo-critical temperature. The flow and heat transfer characteristics of supercritical R1233zd(E) in different tubes, especially in the mini tube, are different. The applicability of three typical buoyancy criteria to this study is discussed, and the results show that two of three typical buoyancy criteria can be used to predict the buoyancy effect of supercritical R1233zd(E) in this study, but the thresholds of mini tube and ordinary tubes are different. Finally, a new heat transfer correlation is developed for supercritical R1233zd(E) by using the piecewise fitting method with pseudo-critical temperature as the point of division. The average relative deviation of the correlation is 0.57 % and the root mean square deviation is 0.87 %.